RANCANG BANGUN APLIKASI PENGELOLAAN DATA ALUMNI UNTUK MENDUKUNG ADMINISTRASI AKADEMIK DI POLITEKNIK NEGERI MANADO - Panadjo, Florecita; Mesak, Brayen Gabriel; Waroh, Anthoinete; Pairunan, Toban T.; Kimbal, Anthon A. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study developed a web-based PHP and MySQL application for alumni data management at Politeknik Negeri Manado using the Waterfall method, replacing inefficient manual processes. The application includes admin authentication, alumni data CRUD, search, filter, and automated report generation. SUS evaluation yielded a score of 84.2 (